Social Factors Affecting Joining Political Violence Groups: An analysis of the role of the environment and the family - Abouelkheir, Omaima Mohamed Elsayed (Al-Adab Journal, 2019)
This study strives to uncover the most important and influential factors in the growing phenomenon of political violence in Egyptian society in the current period. The study was based on a qualitative sample of 50 members of the Jemaah Islamiyah Organization who were sentenced and are spending long periods of time in the state penal institutions. the study used the case study manual as a data collection tool. One of the most important discoveries of this study is the strength of the political factors on the social factors in the growing phenomenon of political violence in Egyptian society, where the state or the political system is the main engine of political violence by the organization of the Islamic Group in order to change and reform the state. The impact of peer groups on joining these groups is also strongly influenced by the effect of the family on the involvement of some members in political violence groups, but as a secondary factor its influence cannot be compared to the external factors of the political system - members of the organization - the peer group These results are consistent with the literature of political violence and many field studies on the subject.